BIOSYNTHESIS OF HYDRASTINE AND BERBERINE - James, Richard Gear (My University, 2024)
The biosynthesis of hydrastine and of berberine was investigated by feeding radioactive tyrosine and dopamine to Hydrastis canadensis L. It was shown that both hydrastine and berberine are specifically derived from two molecules of tyrosine, but that the ratio of incorporation of the two molecules of radiotyrosine was not unity, but varied with time. Dopamine was also incorporated into hydrastine without randomization, but only one molecule was utilized. The results, which are consistent with Robinson's hypothesis of biogenesis, throw light on some of the individual steps of the biosynthetic path by which hydrastine and berberine are derived.
Keywords: Philosophy; Chemistry